Mathematics anxiety maneuver in the process of creative thinking: A review of students in explaining the proving in front of the class - Kristianus Viktor Pantaleon; Marselus Ruben Payong; Fransiskus Nendi; Emilianus Jehadus; Valeria Suryani Kurnila (STKIP PGRI Banjarmasin, 2020)
This qualitative research aims to reveal in depth the intervention of mathematical anxiety in creative thinking when the subject explains the questions of proof in front of the class. The research subjects were two prospective mathematics teacher students, one was a student with a high level of mathematics anxiety (CT) while the other was a student with a low level of mathematics anxiety (CR), but both subjects had equal mathematical abilities. Data were analyzed qualitatively through five stages: data analysis, data validity checking, data reduction, data presentation, and drawing conclusions. The results of this study indicate that both subjects can produce unique (original) ways of solving problems, but CR is more smooth, detailed, and flexible in thinking. In addition, this study also found that CR is not careful in thinking so that she makes small mistakes that are not intentional.